Upaya Guru Bimbingan Konseling dalam Meningkatkan Prestasi Belajar Siswa SMP Negeri 20 Surakarta - Della Nur Shayidah; Dhian Riskiana Putri (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2025)
Learning is a behavior that each individual acquires to obtain a new change in behavior as a whole, in order to have the necessary abilities, skills and knowledge. Of course, students need the help of a teacher to support them, one of those who can help is the BK teacher. One of the duties of guidance and counseling teachers is to develop students according to their needs. Learning achievement is the result achieved or obtained by a child in the form of grades. This research method uses qualitative. The conclusion obtained is that BK teachers carry out guidance programs based on the assessments that have been carried out, the counseling theories used by each BK teacher are different from each other.